Pemanfaatan Sabut Kelapa Sebagai Bahan Dasar Tinta Batik Hitam Melalui Proses Pirolisis - Hapsari, Putri Uniqa Hapsari; Kusumantoro, HB. Rudi; Djonaedi, Emmidia (Program Studi Pendidikan Kimia, FKIP, Universitas Riau, 2025)
Batik is a world-recognized cultural heritage of Indonesia, but the batik industry still relies on synthetic dyes that pollute the environment, especially water pollution. This study aims to develop natural black batik ink from coconut fibre through pyrolysis and analyse its colour density. The process is carried out by heating coconut fibre at 150-250°C to produce charcoal, which is then pulverized into pigments. The pigments were mixed with distilled water (variation of 1-7 g pigment and 6-12 mL distilled water) and tested for density using a spectrodensitometer. The results showed that the formulation of 6 grams of pigment and 11 mL of distilled water produced the highest concentration (2.68). The average concentration of all samples reached 2.57, indicating the consistency of pigment quality. This study proves that the ratio of pigment and solvent affects colour density, while providing an environmentally friendly solution by utilizing coconut fibre waste as a natural dye with economic value.